Reversing chemoresistance of malignant glioma stem cells using gold nanoparticles - Orza A (Dove Medical Press, 2013)
Anamaria Orza,1,2 Olga Soriţău,3 Ciprian Tomuleasa,3,4 Liliana Olenic,5 Adrian Florea,4 Ovidiu Pana,5 Ioan Bratu,5 Emoke Pall,6 Stefan Florian,3 Dan Casciano,2 Alexandru S Biris21Faculty of Chemistry and Chemical Engineering, Babes-Bolyai University, Cluj-Napoca, Romania; 2Center for Integrative Nanotechnology Sciences, University of Arkansas at Little Rock, Little Rock, AR, USA; 3Ion Chiricuta Oncology Institute, Cluj-Napoca, Romania; 4Faculty of General Medicine, Iuliu Hatieganu University of Medicine and Pharmacy, Cluj-Napoca, Romania; 5National Institute for Research and Development of Isotopic and Molecular Technologies, Cluj-Napoca, Romania; 6Department of Research, University of Agriculture and Veterinary Medicine, Cluj-Napoca, RomaniaAbstract: The low rate of survival for patients diagnosed with glioblastoma may be attributed to the existence of a subpopulation of cancer stem cells. These stem cells have certain properties that enable them to resist chemotherapeutic agents and ionizing radiation. Herein, we show that temozolomide-loaded gold nanostructures are efficient in reducing chemoresistance and destroy 82.7% of cancer stem cells compared with a 42% destruction rate using temozolomide alone. Measurements of in vitro cytotoxicity and apoptosis indicate that combination with gold facilitated the ability of temozolomide, an alkylating drug, to alter the resistance of these cancer stem cells, suggesting a new chemotherapy strategy for patients diagnosed with inoperable recurrent malignant glioma.Keywords: gold nanoparticles, drug delivery, temozolomide therapy, temozolomide stability, cancer stem cells, recurrent high-grade gliomas